Mewujudkan Keadilan Iklim: Urgensi Regulasi bagi Yayasan, Kepastian Hukum dan Mitigasi Perubahan Iklim di Indonesia - Salim Abdurrahman; Sirait, Ningrum Natasya; Tri Murti Lubis (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2025)
The climate change mitigation agenda in Indonesia urgently requires the realization of climate justice through inclusive approaches that involve non-state actors, such as foundations. As nonprofit legal entities, foundations possess strategic potential to implement climate change mitigation programs, particularly those based on carbon market mechanisms. However, to date, there is a lack of clear legal certainty allowing foundations to participate lawfully in such initiatives. This study aims to address three core questions: (1) What is the legal basis for foundations to engage in carbon-based climate mitigation programs? (2) How does the absence of carbon-related terminology in a foundation’s statutes (AD/ART) affect its legal authority? (3) What is the ideal regulatory framework that could ensure legal certainty for foundations in carrying out climate mitigation programs? This research employs a normative legal approach using library research methods, focusing on the analysis of relevant legislation and institutional documents of foundations involved in climate initiatives. The findings reveal that there is no explicit legal basis regulating the role of foundations in carbon-based mitigation programs. The absence of carbon-related nomenclature in the statutes of foundations creates the risk of exceeding their legal authority. Although Article 46 paragraph (2) point (d) of Presidential Regulation No. 98 of 2021 refers to “the public” as an actor in the implementation of the Carbon Economic Value (NEK), no derivative regulation clarifies whether foundations, as legal entities, are included in this category. The theoretical implication of this study emphasizes the need to reformulate the concept of climate justice within Indonesia's environmental law to formally recognize the institutional role of civil society. Such recognition is crucial for integrating legal certainty, regulatory effectiveness, and collective participation in the global climate mitigation agenda.